Clinical manifestations and associated factors in acquired hypoaldosteronism in endocrinological practice - Ruiz-Sánchez, Jorge Gabriel; Calle-Pascual, Alfonso Luis; Rubio-Herrera, Miguel Ángel; De Miguel Novoa, María Paz; Gómez-Hoyos, Emilia; Runkle, Isabelle (Frontiers in Endocrinology, 2022)
Introduction Hypoaldosteronism can be congenital or acquired, isolated or part of primary adrenal insufficiency, and caused by an aldosterone deficit, resistance, or a combination of both. Reduced mineralocorticoid action can induce a decrease in urine K+ and H+ excretion and an increase in urine Na+ excretion, leading to hyperkalemia, and/or hyponatremia, often combined with metabolic acidosis. We aimed to characterize the clinical manifestations of hypoaldosteronism, and their associated factors. Methods Retrospective analysis of 112 episodes of hypoaldosteronism diagnosed in 86 adult patients from 2012-2019 by the Endocrinology and Nutrition Department of a tertiary hospital. The frequency of hyperkalemia, hypovolemic hyponatremia (HH) and metabolic acidosis (MA), and their associated factors were evaluated. Results Patients had a median age of 77 [65 – 84], 55.4% were male. 94.6% cases showed hyperkalemia, 54.5% HH, and 60.3% MA. The mean serum K+ of all cases was 5.4 ± 0.5 mmol/L, Na+: 132.1 ± 6.3 mmol/L, HCO3: 22.6 ± 3.3 mmol/L. Hypoaldosteronism was isolated in the majority of cases: only 6/112 (5%) had primary adrenal insufficiency. Hypovolemia was associated with hyponatremia and a more florid clinical presentation. HH was associated with a combined presence of aldosterone-lowering and mineralocorticoid resistance factors. MA was associated with the presence of mineralocorticoid resistance factors. Conclusions Hypoaldosteronism in adult endocrinological clinical practice is primarily isolated, and acquired. It predisposes not only to the development of hyperkalemia and MA, but also to that of HH. Hypoaldosteronism must be considered in the differential diagnosis of HH with urinary sodium wasting.